Review of the genus Scolothrips (Insecta, Thysanoptera, Thripidae) from Japan - Masumoto, Masami; Ohno, Suguru; Ganaha-Kikumura, Tomoko; Miyagi, Akiko; Okajima, Shûji (Zootaxa, 2012)
Three species of the genus Scolothrips Hinds, all predatory on spider mites [Tetranychidae], are recorded here from Japan,with S. rhagebianus Priesner newly recorded from this country. These three species, including S. asura Ramakrishna & Margabandhu and S. takahashii Priesner, are re-described.